Introduction of meta-analysis: What, why and who - Wong, Li Ping; Ab Sallam, Atiya; Chan, Edwin Shih Yen; Lang, Chim Choy (Faculty of Medicine, University of Malaya, 2000)
Meta-analysis is a method of review that summarises the results of previous research of the same particular issue in a systematic and quantitative way. A meta-analysis that properly combines results from different studies will average out differences caused by random variation and produce a more precise estimate of the true effect. It may also detect and investigate heterogeneity among studies thus providing a deeper understanding of clinical dilemmas and guidance on resolving them.in this way a meta-analysis will be a better guide to practice than an individual study. Meta-analysis also has its limitations as it is largely dependent on the quality of published data and requires careful planning and execution of a valid protocol, together with cautious interpretation of the results.